2012
DOI: 10.2478/v10045-012-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Mycotoxins in Organic Spelt Products

Abstract: Mycotoxins have a proven toxic effect on the health of humans and animals. Nowadays, there is a focus on having a healthy lifestyle and consuming organic foods. High quality grain products, especially spelt products, which are an important element of a well-balanced diet have become more popular. The aim of this study was to determine the mycotoxin content in spelt products available on the Polish market. Spelt products were collected in 2009 and 2010 in eastern Poland. The Enzyme-Linked ImmunoSorbent Assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In one of the few studies reporting its presence in spelt products, only 0.5% and 2% of the total sample number contained detectable AFB 1 levels during the 2 years (2010 and 2011) investigation, respectively. 32 Effects of climate change and continuous innovation of agricultural practice cause a wider spectrum of pathogen species invading cereals in the field and consequently secondary metabolites left in the crop at the time after harvest. According to Medina et al 25 changes in climatic conditions such as higher temperatures, water stress and CO 2 stimulate AFB 1 biosynthesis in cereals.…”
Section: Results and Discussion Afb 1 Content In Speltmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the few studies reporting its presence in spelt products, only 0.5% and 2% of the total sample number contained detectable AFB 1 levels during the 2 years (2010 and 2011) investigation, respectively. 32 Effects of climate change and continuous innovation of agricultural practice cause a wider spectrum of pathogen species invading cereals in the field and consequently secondary metabolites left in the crop at the time after harvest. According to Medina et al 25 changes in climatic conditions such as higher temperatures, water stress and CO 2 stimulate AFB 1 biosynthesis in cereals.…”
Section: Results and Discussion Afb 1 Content In Speltmentioning
confidence: 99%
“…Generally, available literature provides scant information on the aflatoxin contamination of spelt in comparison to other cereals. Solarska et al 32 reported relatively low level of aflatoxins in naturally contaminated organic spelt products collected in Poland. Our recent study 21 indicated the occurrence of A. flavus on spelt wheat in Serbia that confirms the importance of the examination of the spelt response under different storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The consummation of spelt products helps to reduce the cholesterol level in blood and fosters the circulatory system [32]. This wheat species has been also known for the high resistance to unsupportive environmental factors.…”
Section: Triticum Spelta Lmentioning
confidence: 99%
“…They are effective in the economic aspect due to a reduction of cost by around 2-3 times [9]. One of the most common phytopatogenic fungi infected root and tuber crops are fungi belonging to the genera Fusarium and Penicillium; their toxins contaminate grain, silage, and animal feed [10,11,12]. The high danger of mycotoxins is that they exert toxic effects in extremely small amounts and are able to intensively diffuse into foodstuffs and cause various diseases that anything from acute skin damage to cancer.…”
Section: Introductionmentioning
confidence: 99%